Managing innovation : integrating technological, market and organizational change - Tidd, Joseph, 1960-; Bessant, J. R. (Hoboken : Wiley, 2021)
'Innovative firms outperform, in both employment and sales, firms that fail to innovate [1]. We know that those organizations that are consistently successful at managing innovation outperform their peers in terms of growth, financial performance, and employment and that the broader social benefits of innovation are even greater [2]. However, managing innovation is not easy or automatic. It requires skills and knowledge, which are significantly different to the standard management toolkit and experience, because most management training and advice are aimed to maintain stability, hence the most sought after degree is an MBA - Master of Business Administration. As a result, most organizations either simply do not formally manage the innovation process or manage it in an ad hoc way. Studies confirm that only around 12% of organizations successfully manage innovation, and only half of these organizations do so consistently across time [3]. Since the first edition of Managing Innovation was published in 1997, we have argued consistently that successful innovation management is much more than managing a single aspect, such as creativity, entrepreneurship, research and development, or product development [4]. Our companion texts deal with such issues more fully [5], but here we continue to promote an integrated process approach, which deals with the interactions between changes in markets, technology, and organization. In this seventh edition, we continue our tradition of differentiating our work from that of others by developing its unique characteristics: Strong evidence-based approach to the understanding and practice of managing innovation, drawing upon thousands of research projects, and'Research Notes' on the very latest research findings. Managing Innovation had more than 11,000 citations in Google Scholar; Practical, experience-tested processes, models, and tools, including'View,' first-person accounts from practicing managers on the challenges they face managing innovation; Extensive additional interactive resources, available from the Wiley Book Companion Site (BCS), including video, audio pod casts, innovation tools, interactive exercises, and tests to help apply the learning. Further video is available on our YouTube channel, innovation masters)'--
Revised edition of the authors' Managing innovation, [2018].
Includes index.
Buku bacaan asas siswazah Fakulti Ekonomi dan Pengurusan.
Keywords: Technological innovations -- Management; Industrial management; Technological innovations; Organizational change